Attitudes and Language Proficiency of College Students at Catanduanes State University Panganiban Campus - Salvador, Juvelyn (JPAIR Institutional Research, 2022)
The study determined the attitudes toward the English language, the general proficiency level of 60 selected first-year college students, language structure, reading comprehension, and vocabulary. This was conducted to solve current issues of reading comprehension difficulties and poor linguistic competence in English subjects. It utilized descriptive research. Findings revealed “zero highly unfavorable” attitudes towards English; 2 “highly favorable.” For language structure, half of them were “slightly proficient,” 26 (43.33%) “Proficient,” 2 (3.33%) “Moderately proficient,” and 2 (3.33%) “Very poor.” No one obtained a “highly proficient” rating. The mean score: was 14.02, 4.59 standard deviation. The overall proficiency was “slightly proficient.” For vocabulary (context clues, antonym, analogy, denotation, and connotation), 29 (48.33%) rated “Slightly proficient,” 23 (38.33%) demonstrated “poor” performance, 6 (10%) were “moderately proficient” only 2 (3.33%) obtained “very poor” rating. The mean score is 13.52/ 4.15 standard deviation, a “slightly proficient” overall rating. “Connotation”- highest with a 3.50 mean score; lowest on “analogy “1.42 mean. For reading comprehension, 29 (48.33%) had “Slightly adequate” proficiency, 25 (41.67%) had “Poor” performance, 4 (6.67%) had a “Very poor” rating, 2(3.33%) had “Moderately proficient”- mean score 12.12, 3.51 standard deviation. “Poor” overall proficiency. “Forming opinions”- easiest; “drawing conclusion “- most difficult. The general proficiency level was “slightly proficient,” with a 42.23 mean. Respondent’s language structure and vocabulary are “slightly proficient, while “Poor” in reading comprehension.